Functional gene-mining for salt-tolerance genes with the power of Arabidopsis - Du, Jin (2008)
Here we report on a functional gene-mining method developed to isolate stress tolerance genes without any prior knowledge of the genome or genetic mapping of the source germplasms. The feasibility of this approach was demonstrated by isolating novel salt stress tolerance genes from salt cress (Thellungiella halophila), an extremophile that is adapted to a harsh saline environment and a close relative of the model plant Arabidopsis thaliana. This gene-mining method is based on the expression of salt cress cDNA libraries in Arabidopsis. A cDNA expression library of the source germplasm, salt cress, was constructed and used to transform Arabidopsis via Agrobacterium-mediated gene transfer. A transgenic seed library consisting of >125 000 independent lines was generated and screened for salt-tolerant lines via a high-throughput genetic screen. A number of salt-tolerant lines were isolated, and the salt cress cDNAs were identified by PCR amplification and sequencing. Among the genes isolated, several novel small protein-encoding genes were discovered. The homologs of these genes in Arabidopsis have not been experimentally analyzed, and their functions remain unknown. The function of two genes isolated by this method, ST6-66 and ST225, and their Arabidopsis homologs, were investigated in Arabidopsis using gain- and loss-of-function analyses, and their importance in salt tolerance was demonstrated. Thus, our functional gene-mining method was validated by these results. Our method should be applicable for the functional mining of stress tolerance genes from various germplasms. Future improvements of the method are also discussed.